The Effect of Personality, Organizational Climate and Job Satisfaction on Teachers Organizational Citizenship Behavior at Public Vocational High School in DKI Jakarta Province - ., Asari; Abdullah, Thamrin; ., Wibowo (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this research to study the effect of personality, organizational climate and job satisfaction on Organizational Citizenship Behavior of teachers at public vocational high schools in Central Jakarta Administration city of Jakarta DKI Jakarta province. This study uses a quantitative approach with survey method. The population of this research is all civil servant teachers at 14 public vocational high schools in Central Jakarta Administration city area. The number of samples of the study were 212 teachers who were taken with the Slovin formula of a population of 451 teachers. The data collection research by questionnaires and then analyzed for statistically descriptive and inferential statistical path analysis. Based on the research hypothesis testing of the study found,  1)there is a direct positive effect of Personality on Organizational Citizenship Behavior, 2)there is a direct positive effect of Organizational Climate on Organizational Citizenship Behavior, 3)there is a direct positive effect of job satisfaction on Organizational Citizenship Behavior, 4)there is a direct positive effect of Personality on Job Satisfaction, and 5)there is a direct positive effect of Organizational Climate on Job Satisfaction